Women writers of Latin America : intimate histories - García Pinto, Margarita (University of Texas)
Incluye textos sobre las siguientes escritoras latinoamericanas: Isabel Allende, Albalucía Angel, Rosario Ferré, Margo Glantz, Sylvia Molloy, Elvira Orphée, Elena Poniatowska, Marta Traba, Luisa Valenzuela, Ida Vitale.